A reforma do estado após a emenda constitucional 45/04: a reforma do poder judiciário - Rodovalho, Maria Fernanda de Toledo (2012)
This thesis aims to analyze the reform of the Judiciary from the 45th Constitutional Amendment, specifically regarding the coexistence of criteria of efficiency and justice. The study was structured using the agenda-setting theoretical model and data contained in publications, books, court decisions. The intention was to demonstrate how problems are defined and solutions are presented in a context of ambiguity. Finally, we observe the impact of changes in the still incomplete redefinition of relations between Judiciary and society.